Employment stability in Polish civil service versus plans of reducing the scale of government administration - Szczepański, Marek (Journal of Public Governance, 2012)
The article concerns aspects of employment stability in Polish civil service in the context of the government’splans of reducing the costs of functioning and scale of government administration. The author presents theoretical assumptions of higher employment stability in civil service compared to other professional groups and discusses formal grounds of employment stability in Polish civil service as well as practical problems relating to terminating employment relationships with civil servants. What is more, he introduces the results of research concerning the influence of employment stability on the attitude of civil servants. The article also discusses the 2010 attempt to reduce employment in government administration. To conclude, the author offers some suggestions concerning employment reduction in government administration.